Multiple Extrauterine Adenomyomas Presenting in Upper Abdomen and Pelvis: A Case Report and Brief Review of the Literature - Mana Moghadamfalahi; Daniel S. Metzinger (Hindawi Limited, 2012)
Adenomyomas are benign tumors composed of smooth muscle and endometrial tissue. These tumors usually arise from the myometrium. Extrauterine adenomyomas are rare with only a few case reports available in the literature. Here, we report an unusual case of multiple adenomyomas in a 39-year-old woman six years after hysterectomy for multiple leiomyomata. To the best of our knowledge, this is the first case of extrauterine adenomyoma presenting as an upper abdominal mass.